The Ecological Crisis and Indonesian Muslim Organizations’ Responses - Indria Hartika Rukmana (International Journal of Interreligious and Intercultural Studies, 2020)
This paper focuses on Muslim initiatives on saving the environment. It examines various attempts, commitments, statements, and declarations by Muslims around the world to see how these have affected two mass Muslim organizations in Indonesia, namely Nahdhatul Ulama and Muhammadiyyah. This paper describes initiatives that have been proposed by international and national Muslim organizations on the environment and analyzes how these initiatives have been implemented by Nahdhatul Ulama and Muhammadiyah organizations in Indonesia based on their two publications about plastic waste. In addition, this paper explores various initiatives in the world that commit to protect nature, carried out in numerous ways ranging from theological to practical. In particular the efforts to overcome plastic waste in An-Nur mosque in Bantul by reducing the use of plastic waste in several mosque events as well as conducting training on organic and non-organic waste sorting. In addition, practical paths are carried out by several environmental activists in Yogyakarta who make several environmentally friendly products and trash banks as an alternative to advocating for waste. Various commitments were built to lead to a clean environment free of garbage. It is important to see aspects of the faith that play a strong role in the awareness of the importance of protecting the earth in the future.